Thermodynamics of Intragenic Nucleosome Ordering - G. Chevereau; L. Palmeira; Claude Thermes; A. Arnéodo; Cédric Vaillant (2009)
The nucleosome ordering observed in vivo along yeast genes is described by a thermodynamical model of nonuniform fluid of 1D hard rods confined by two excluding energy barriers at gene extremities. For interbarrier distances $\mathcal{L}\ensuremath{\lesssim}1.5\text{ }\text{ }kbp$, nucleosomes equilibrate into a crystal-like configuration with a nucleosome repeat length (NRL) $\mathcal{L}/n\ensuremath{\sim}165\text{ }\text{ }bp$, where $n$ is the number of regularly positioned nucleosomes. We also observe ``bistable'' genes with a fuzzy chromatin resulting from a statistical mixing of two crystal states, one with an expanded chromatin (NRL $\ensuremath{\sim}\mathcal{L}/n$) and the other with a compact one (NRL $\ensuremath{\sim}\mathcal{L}/(n+1)$). By means of single nucleosome switching, bistable genes may drastically alter their expression level as suggested by their higher transcriptional plasticity. These results enlighten the role of the intragenic chromatin on gene expression regulation.